Boronate affinity materials for separation and molecular recognition: structure, properties and applications. (17th September 2015) - Li, Daojin; Chen, Yang; Liu, Zhen
Abstract : We critically survey recent advances in boronate affinity materials for separation and molecular recognition, which have gained rapid development recently. Abstract : Boronate affinity materials, as unique sorbents, have emerged as important media for the selective separation and molecular recognition of cis -diol-containing compounds. With the introduction of boronic acid functionality, boronate affinity materials exhibit several significant advantages, including broad-spectrum selectivity, reversible covalent binding, pH-controlled capture/release, fast association/desorption kinetics, and good compatibility with mass spectrometry. Because cis -diol-containing biomolecules, including nucleosides, saccharides, glycans, glycoproteins and so on, are the important targets in current research frontiers such as metabolomics, glycomics and proteomics, boronate affinity materials have gained rapid development and found increasing applications in the last decade. In this review, we critically survey recent advances in boronate affinity materials. We focus on fundamental considerations as well as important progress and new boronate affinity materials reported in the last decade. We particularly discuss on the effects of the structure of boronate ligands and supporting materials on the properties of boronate affinity materials, such as binding pH, affinity, selectivity, binding capacity, tolerance for interference and so on. A variety of promising applications, including affinity separation, proteomics, metabolomics, disease diagnostics and aptamer selection, are introduced with main emphasis on how boronate affinity materials can solve the issues in the applications and what merits boronate affinity materials can provide.